Predicting Viral Failure in Human Immunodeficiency Virus Perinatally Infected Youth With Persistent Low-Level Viremia on Highly Active Antiretroviral Therapy. (19th May 2018) - Pereira, Ruth; Ludwig, David A; Mathew, Sunil; Flores, Claudia; Dominguez, Sady; Gonzalez, Ivan; Rivera-Hernandez, Delia; Scott, Gwendolyn B; Mitchell, Charles D
Abstract: Background: Less than optimal adherence with antiretroviral therapy occurs commonly among human immunodeficiency virus HIV)-infected youth. In this study, our object was to identify patterns in the prefailure measurement of viral load (VL) that can reliably predict virological failure (VF) in HIV perinatally infected youth on highly active antiretroviral therapy (HAART). Methods: We conducted a retrospective chart review of HIV-infected youth with low-level viremia (LLV), defined as an HIV VL between the lower limits of detection (20–75 copies/mL) and 1000 copies/mL. All patients were perinatally infected, under 22 years of age, observed for at least 24 months of consecutive follow-up between May 2008 and July 2014, and received their HIV care at the University of Miami Miller School of Medicine. Of the 349 subjects screened, 100 were eligible for analysis. Virological failure was defined as 3 or more consecutive VLs greater than 1000 copies/mL. Multiple logistic regression and receiver operator characteristic curves were used to identify patterns in VL that ultimately resulted in VF. Results: Fifteen of the 100 patients experienced VF. Higher log10 mean VL, positive slope of the VL (log10 copies/mL per day), and fewer clinic visits were associated with a higher probability of VF. Sensitivity and specificity were .87 and .95, respectively. Resistance was not found in 12 of 15 patients with VF. Conclusions: Patients with LLV that had fewer clinic visits and a trend toward increasing VLs had an increased risk of VF. Noncompliance seems to be a major component of VF. Physicians should emphasize the critical nature of medication adherence.